Aegyptiaca in der nördlichen Levante Eine Studie zur Kontextualisierung und Rezeption ägyptischer und ägyptisierender Objekte in der Bronzezeit - Ahrens, Alexander (Orbis Biblicus et Orientalis. Series Archaeologica, 2020)
In this interdisciplinary study, Alexander Ahrens examines Egyptian objects found in the northern Levant (covering the modern states of Lebanon, Syria, and parts of Turkey) in archaeological contexts dated to the second millennium BCE. Drawing on methods from archaeology and sociocultural theory, he provides a characterization of the perception and accompanying emulation of Egyptian material culture within northern Levantine elite spheres. Analyzing many of the artifacts' find contexts, he proposes a new way to explore their ancient perception and reception through the study of archaeological and historical sources. The book thus enhances our understanding of the complexity and diversity of intercultural relations in the eastern Mediterranean during the Bronze Age.